FRI0415 Patients' Illness Perceptions Are Associated with Physical Health-Related Quality of Life Independent of Psychological Distress and Disease Severity in Primary Sjogren's Syndrome, Systemic Lupus Erythematosus and Rheumatoid Arthritis. (10th June 2014) - Kotsis, K.; Hyphantis, T.; Tsifetaki, N.; Voulgari, P.V.; Drosos, A.A.
Abstract : Background: Illness perceptions and psychological distress are important in determining outcomes in rheumatic diseases. Objectives: We aimed to assess illness perceptions and psychological distress and their associations with Physical health-related quality of life (HRQoL) in primary Sjogren's Syndrome (pSS), Systemic Lupus Erythematosus (SLE) and Rheumatoid arthritis (RA). Methods: In 57 pSS, 75 SLE and 199 RA patients we administered the Patient Health Questionnaire (PHQ-9), the Symptom Distress Check-List (SCL-90-R) and the Brief-Illness Perception Questionnaire (B-IPQ) to assess psychological variables and the World Health Organization Quality of Life Instrument, Short-Form (WHOQOL-BREF) to assess HRQoL. Hierarchical regression models were used adjusting for demographic and clinical variables. Results: The prevalence of clinically significant depressive symptoms (PHQ-9≥10) was 24.6% in pSS, 29.3% in SLE and 25.1% in RA. Patients with pSS showed little understanding of their disease ( comprehensibility ) and attributed more symptoms to their illness ( identity ) compared to SLE and RA. Depressive symptoms and concerns about the consequences of the disease were associated with Physical HRQoL independently of pain, disease duration and disease severity in all three diseases. In pSS, however, the patients' worries about the consequences of their illness totally mediated the relationship of pain with Physical HRQoL. Moreover, SLE patients' concerns about numerous bodily symptoms attributed to the illness ( illness identity ) were also important independent correlates of Physical HRQoL. Conclusions: These findings indicate that patients' illness perceptions are important correlates of HRQoL in these disease groups and encourage the design of psychotherapeutic trials targeting disease-related cognitions in an attempt to improve patients' HRQoL. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3177